Ethics and professional relationships (Portuguese Journal of Family Medicine and General Practice, 2008)
Patient referral is the key for continuing care. Nevertheless, referral procedures have many omissions and there are failures either on quality or on contents of the message, as well as on its form and timing. In Portugal the problem has special importance and there are some national and international studies reporting bad outcomes regarding information exchanges between primary and hospital care. Lack of co-ordination in care causes health costs, professional dissatisfaction and health damages for patients. The authors raised some ethical issues about professional relationships, medical accountability, and health consequences for patients. This originates from a bad clinical practice in the referral procedures and in directing the patient throughout the health system.
Keywords: Referral; Ethic